Efficient All-Optical Helicity Dependent Switching of Spins in a Pt/Co/Pt Film by a Dual-Pulse Excitation - Yamada, Kihiro T.; Kimel, Alexey V.; Prabhakara, Kiran Horabail; Ruta, Sergiu; Li, Tian; Ando, Fuyuki; Semin, Sergey; Ono, Teruo; Kirilyuk, Andrei; Rasing, Theo (Frontiers in Nanotechnology, 2022)
All-optical helicity dependent switching (AO-HDS), deterministic control of magnetization by circularly polarized laser pulses, allows to efficiently manipulate spins without the need of a magnetic field. However, AO-HDS in ferromagnetic metals so far requires many laser pulses for fully switching their magnetic states. Using a combination of a short, 90-fs linearly polarized pulse and a subsequent longer, 3-ps circularly polarized pulse, we demonstrate that the number of pulses for full magnetization reversal can be reduced to 4 pulse pairs in a single stack of Pt/Co/Pt. The obtained results suggest that the dual-pulse approach is a potential route towards realizing efficient AO-HDS in ferromagnetic metals.